Score Standardization of the European Health Literacy Survey Questionnaire Short Form (HLS-EU-Q16) in a Sample of Brazilian Adults - Fábio L. Mialhe; Flávio Rebustini (Evaluation & the Health Professions, 2026)
Health literacy (HL) is considered by the World Health Organization an important determinant of health, and several instruments have been developed to measure this construct in populations. However, beyond their evidence of validity of content and internal structure, the standards used to interpret the scores of these instruments must also be validated to avoid incorrect classifications and decision-making, a process known as standardization. The purpose of this study was to assess the normative data of scores from the Brazilian version of the European Health Literacy Survey Questionnaire short form (HLS-EU-Q16) in a sample of Brazilian adults. The study involved 783 Brazilian adults with a mean age of 38.6 years. Data were collected using the HLS-EU-Q16 instrument and analyzed using discriminant analysis and decision trees. The results indicated that using a dichotomous criterion to categorize individuals’ HL levels - low and high HL - provided better evidence of validity for discriminating individuals with different HL levels in Brazil than the three-level classification criteria proposed by the instrument’s original authors. The findings of this study reiterate the need to standardize instrument scores for the populations in which they will be used, avoiding incorrect classifications, as well as unnecessary costs to public health.